Risk of depression in elderly people with visual impairment in a municipality in the interior of Ceará (Research, Society and Development, 2022)
Since aging is a landmark of biopsychosocial changes and depression is the psychological disease that most affects this population, this study aims to identify the risk of depression in elderly people with visual impairment in a municipality in the central hinterland of Ceará. The research is exploratory and descriptive, with a quantitative approach and was carried out in the municipality of Piquet Carneiro, Ceará, with a total of 28 elderly people with acquired visual impairment. Data were collected from the socioeconomic interview and a form-like instrument containing the Geriatric Depression Scale with 15 questions. To analyze the collected data, the SPSS program, version 21.0, was used. The work is protected in Resolution No. 466/2012 of the National Health Council. During the verification of these findings, it was possible to notice that the age group with the highest number of participants was 70 years or older, with a predominance of females, widowed marital status, low education and monthly income of 1 to 2 minimum wages. From the responses with the EDG-15, it was possible to perceive some depressive symptoms present. Questions 2, 9 and 15 were the most scored by all respondents, bringing up feelings such as isolation, sadness and hopelessness on their part, thus exposing the depression rate for these participants of 54%. The results reinforce the need to study and implement more health promotion and prevention actions with a focus on depression in the elderly, especially those with disabilities.